Determinants of a Holistic Social Commerce Model for Saudi Arabia - Aljaafari, Mohammed Abdullatif H (Curtin University, 2022)
This study aims to identify the required factors to develop and evaluate a social commerce model for Saudi Arabia. A mixed-methods approach was adopted to assess the model critically, and substantial theoretical and practical contributions were aligned with the goals of Saudi Vision 2030. The study outcomes were drawn from the model to support Saudi Arabia, and the recommendations were derived from the model to assist Saudi Arabia stakeholders and practitioners in implementing s-commerce successfully.